Integrating labor awareness to energy-efficient production scheduling under real-time electricity pricing: An empirical study. (1st December 2017) - Gong, Xu; Van der Wee, Marlies; De Pessemier, Toon; Verbrugge, Sofie; Colle, Didier; Martens, Luc; Joseph, Wout
Abstract: With the penetration of smart grid into factories, energy-efficient production scheduling has emerged as a promising method for industrial demand response. It shifts flexible production loads to lower-priced periods to reduce energy cost for the same production task. However, the existing methods only focus on integrating energy awareness to conventional production scheduling models. They ignore the labor cost which is shift-based and follows an opposite trend of energy cost. For instance, the energy cost is lower during nights while the labor cost is higher. Therefore, this paper proposes a method for energy-efficient and labor-aware production scheduling at the unit process level. This integrated scheduling model is mathematically formulated. Besides the state-based energy model and genetic algorithm-based optimization, a continuous-time shift accumulation heuristic is proposed to synchronize power states and labor shifts. In a case study of a Belgian plastic bottle manufacturer, a set of empirical sensitivity analyses were performed to investigate the impact of energy and labor awareness, as well as the production-related factors that influence the economic performance of a schedule. Furthermore, the demonstration was performed in 9 large-scale test instances, which encompass the cases where energy cost is minor, moderate, and major compared to the joint energy and labor cost. The results have proven that the ignorance of labor in existing energy-efficient production scheduling studies increases the joint energy and labor cost, although the energy cost can be minimized. To achieve effective production cost reduction, energy and labor awareness are recommended to be jointly considered in production scheduling. Graphical abstract: Highlights: Integration of labor awareness in energy-efficient production scheduling for industrial demand response. Empirical study in a plastic bottle manufacturer. Extensive production-economic sensitivity analyses. Important finding: labor awareness is indispensable in energy-efficient production scheduling.